Perception of intensive care among survivor of critical illness in a tertiary care center - Pant, Chiranjibi; Kumar Shrestha, Bipin; Manandhar, Naresh (Journal of Chitwan Medical College, 2024)
Background: The ICU is a specialized unit for critically ill patients, requiring constant monitoring and support. Patients often experience discomfort due to illness, procedures, and alarms from monitors and equipment. Negative experiences can impact memory, concentration, and mental health. This study explores ICU survivors’ comfort and safety. Method: A cross-sectional descriptive study was conducted in medical ICU of Shree Birendra Hospital, Chhauni, Nepal between 23 Feb to 23 May 2024 using non probability convenience sampling to include adult patients with ICU stay >24 hours. Ethical approval was obtained. Oriented conscious patient perceptions were assessed during ICU transfer out. Likert scale and 24 items Intensive Care Experience Questionnaire with four main domains were used. Perception score, gender and length of stay were analysed in SPSS using t-test. A p-value <0.05 was considered significant. Result: Out of 43 critically ICU patients, 26(60%) were male, mean age 60.2±19.27 years, ICU stay 6.5±4.5 days. Nineteen patients (44%) had respiratory failure due to chronic obstructive lung disease, and 21(48%) used non-invasive ventilation and 8(18.6%) mechanically ventilated. During ICU stay, 32(74%) were aware of surroundings, 24(56%) had frightening experiences, 25(58%) recalled events, and 24(56%) were satisfied with care. Females reported more fear than males, and increased with longer ICU stay. Conclusion: Most patients (74%) remained aware of ICU surroundings, half of them could recall events, and were generally satisfied with the care. Over half (56%) reported frightening experiences related to illness.